1989
DOI: 10.1007/bf00261186
|View full text |Cite
|
Sign up to set email alerts
|

FemA, a host-mediated factor essential for methicillin resistance in Staphylococcus aureus: Molecular cloning and characterization

Abstract: The methicillin resistance determinant (mec) in Staphylococcus aureus resides on additional DNA not present in isogenic sensitive cells. However, besides mec, other chromosomally determined factors are essential for expression of methicillin resistance. We cloned and characterized a chromosomally determined gene which encodes a factor essential for the expression of methicillin resistance (femA) in S. aureus. femA mapped in chromosomal segment number 18, genetically very distant from the methicillin resistance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
145
1

Year Published

1994
1994
2014
2014

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 190 publications
(152 citation statements)
references
References 24 publications
4
145
1
Order By: Relevance
“…The MurN gene product shares 26% sequence identity with Staphylococcus aureus FemA, which catalyzes the addition of the second and third glycine residues in the branched muropeptide of S. aureus (38,39). Disruption of the femA gene abolishes methicillin resistance in this organism (40). The Fem-ABX proteins have a requirement for aminoacyl-charged tRNAs as substrates for the nonribosomal peptide bond formation of the pentaglycine bridge (40).…”
Section: Peptidoglycan Precursor Substratementioning
confidence: 99%
See 1 more Smart Citation
“…The MurN gene product shares 26% sequence identity with Staphylococcus aureus FemA, which catalyzes the addition of the second and third glycine residues in the branched muropeptide of S. aureus (38,39). Disruption of the femA gene abolishes methicillin resistance in this organism (40). The Fem-ABX proteins have a requirement for aminoacyl-charged tRNAs as substrates for the nonribosomal peptide bond formation of the pentaglycine bridge (40).…”
Section: Peptidoglycan Precursor Substratementioning
confidence: 99%
“…Disruption of the femA gene abolishes methicillin resistance in this organism (40). The Fem-ABX proteins have a requirement for aminoacyl-charged tRNAs as substrates for the nonribosomal peptide bond formation of the pentaglycine bridge (40). The functional and sequence similarity of MurN to these proteins suggested that it also uses aminoacyl-tRNAs as substrates.…”
Section: Peptidoglycan Precursor Substratementioning
confidence: 99%
“…Based on the nucleotide sequences of mecA, femA and femB genes [4,16], the oligonucleotides listed in Table 1 Figure 1 shows electrophoretic patterns of the DNA products after PCR using three representative oxacillin-RSA strains. The DNA fragments of 533, 509 and 651 bp were amplified from mecA, femA, and femB genes, respectively.…”
Section: Polymerase Chain Reactionmentioning
confidence: 99%
“…Besides the mec regulator genes, femA and femB genes on the chromosome have been shown to encode proteins which considerably affect the level of methicillin resistance of S. aureus [16]. Although fem genes were suggested to be specific for S. aureus [17], distribution of these genes in staphylococci has not been fully established.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation